Consumption of single cigarettes and quitting behavior: A longitudinal analysis of Mexican smokers - Barnoya Joaquin; Villalobos Victor; Thrasher James F; Sansores Raul; O'Connor Richard (BMC, 2011)
Abstract Background Previous cross-sectional research has suggested single cigarettes could either promote or inhibit consumption. The present study aimed to assess the effects of single cigarette availability and consumption on downstream quit behavior. Methods We analyzed population-based, longitudinal data from adult smokers who participated in the 2008 and 2010 administrations of the International Tobacco Control Policy Evaluation Survey in Mexico. Results At baseline, 30% of smokers saw single cigarettes for sale on a daily basis, 17% bought singles at their last purchase, and 7% bought singles daily. Smokers who most frequently purchased singles, both in general and specifically to control their consumption, were no more likely to attempt to quit over the 14 month follow-up period than those who did not purchase singles. Frequency of buying singles to reduce consumption had a non-monotonic association with being quit at followup. The odds of being quit was only statistically significant when comparing those who had not bought singles to reduce consumption with those who had done so on a more irregular basis (AOR = 2.30; 95% CI 1.19, 4.45), whereas those who did so more regularly were no more likely to be quit at followup. Frequency of self-reported urges to smoke upon seeing singles for sale was unassociated with either quit attempts or being quit at followup. Conclusions These results suggest that the relationship between singles consumption and quit behavior is complex, with no clear evidence that singles either promote or inhibit downstream quit behavior.